2018
DOI: 10.5219/918
|View full text |Cite
|
Sign up to set email alerts
|

Food safety from a consumers´ point of view: food quality

Abstract: Food safety is a topic that is currently very much and often discussed. This may be a debate among political representatives, representatives of the food industry, but also among consumers, ie. general public. The issue of food safety and quality is very important in view of the growing globalization of economy, whose mission is to encourage food businesses to improve the production process as a whole and competitiveness. As in every sector, the food market faces many problems arising from market opening, busi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As in the study of Nagoya et al [45], most of our participants were satisfied with the market hygiene level, product availability, and quality. This revealed that consumers perceived the efforts made by health authorities and market workers to improve food safety and sale conditions.…”
Section: Discussionsupporting
confidence: 63%
“…As in the study of Nagoya et al [45], most of our participants were satisfied with the market hygiene level, product availability, and quality. This revealed that consumers perceived the efforts made by health authorities and market workers to improve food safety and sale conditions.…”
Section: Discussionsupporting
confidence: 63%
“…New brand awareness affects the formation and the strength of new brand associations, including perceived quality (Amegbe, 2016). Many researchers (Kuksov, 2007) have emphasized it as an essential condition for the competitiveness in the market, which also includes food-quality information (Nagyova et al, 2011). Therefore, buyers started looking for safer and better controlled labelling of food products, the ones made in a more environmentally friendly, authentic, and locally oriented way (Rembialkowska, 2004).…”
Section: New Brand New Product Equity New Product Consistency Qualitmentioning
confidence: 99%
“…Many researchers (Kuksov, 2007;Davcik, 2009) have emphasized it new brand equity as an essential condition for the competitiveness in the market, which also includes food-quality information (Nagyova, Horska, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In ensuring food safety, it is necessary to consider all aspects of the food production chain, because each subject can have a potential impact on food safety (Nagyová et al, 2019). The issue of food safety and quality is very important in view of the growing globalization of economy, whose mission is to encourage food businesses to improve the production process and competitiveness (Nagyová et al, 2018).…”
Section: Introductionmentioning
confidence: 99%